Antecedents of the Utilization of Social Media and its Impact on Micro and Small Enterprises Performances - Yulia Sari; Amir Hidayatulloh (Faculty of Economics, State University of Jakarta., 2019)
This study aimed to analyze the antecedents of the utilization of social media for MSEs and its impact on performances. Performances such as; service performance, sales performance, marketing performance, internal operating performance and innovation performance. The population in this study were MSEs in the Special Region of Yogyakarta, the sampling technique used in this study was purposive sampling with criteria of (1) MSEs locationed in Sleman Regency and (2) MSEs which use social media (Faceebook, Instagram) for marketing purposes. Respondents in this study amounted to 100 MSEs. WarpPLS used for data analysis technique. The results showed that the utilization of social media by MSEs was influenced by interactivity, cost effectiveness and compatibility. Meanwhile, trust does not affect the utilization of social media. The utilization of social media by MSEs has a positive effect on each performances.